Students’ Perceptions on the Use of Duolingo as a Tool for Pronunciation Practice - Narjiani, Roselina Maria; Andayani, Endah Alamsari; Aisyah, Siti (UIBU, 2026)
Pronunciation is a component of spoken English because it affects intelligibility and learners’ confidence in oral communication, yet it often receives limited attention in english classrooms. Mobile language-learning applications offer additional opportunities for practice beyond classroom time. This study explored students’ perceptions of Duolingo as a supplementary tool for pronunciation practice and identified the benefits and challenges they experienced while using it. Employing a descriptive qualitative design, the study involved 21 third-semester students from the English Education Study Program at Universitas PGRI Delta Sidoarjo. Data were collected through closed and open-ended questionnaires and semi-structured interviews, then analyzed using data reduction, data display, and conclusion drawing. The findings indicate that many students perceived Duolingo positively, particularly for supporting repeated listening and speaking practice, providing immediate feedback, and fostering motivation and confidence through gamified features. Interview responses further showed that Duolingo encouraged regular practice in a low-pressure learning environment. However,limitations were reported, including inconsistent voice recognition accuracy, insufficient phonetic or articulatory guidance, and limited emphasis on sentence-level pronunciation practice. Overall, Duolingo is perceived useful for basic pronunciation practice and motivation, but it is not considered a substitute for teacher-led instruction. Integrating Duolingo with classroom pronunciation guidance is recommended to optimize learning outcomes.